EVOLUTION OF MANAGEMENT IN THE INFORMATION TECHNOLOGY DOMAIN TO INCREMENTAL AND TANGIBLE OUTCOME-BASED MODE: ACCELERATED BY THE POSITIVE INFLUENCE OF COVID-19 - et. al., Ravi Kumar Jain (International Journal of Modern Agriculture, 2021)
Management, as the study of the organization and the organizational phenomenon has been an evolving body of knowledge that has particularly been maturing to inculcate the intricacies of knowledge work and the knowledge worker. The trend has been continuous, but the form and messaging have crystallized more with the advent of the twentieth century. Management in Information Technology has also embraced this evolution as it is necessitated by the demands of the knowledge work. From a linear sequential management model to iterative feedback and feed forward driven management methodology, the journey has been continuous. The study analyzed this trend which clearly showed the evolution but also inherent inertia in adapting to this evolution, thus creating limits to the opportunities that it provides. So, the journey from the waterfall model of software development in the Information Technology domain to a ‘V-model’ (software development model), where software development is plotted against software testing and then the iterative models evolved to Agile methodology. But in run-time, the mode to implement Agile through Sprint, scrum, etc. became a mini waterfall. The requirement analysis was based on Work Breakdown Structure, which should ideally have been User story and acceptance criterion, the resource loading, and inherent effort estimation and resource utilization were role-based, such as Project Manager, Technical Architect, Team Leader, Developer, Tester, etc., though it should have been Scrum Master and Scrum Members. Bell curve is being used habitually to measure resource performance within the team. Individual sprints were not leading to production release, which is how it was envisioned but there was some staging environment created where the sprints ended and then did a common User Acceptance Testing which is followed by deployment to production much like the waterfall model. To add to this, puritanical Agile practitioners were necessitating all scrum members to be in the same room for an effective stand-up or scrum meeting, which is almost impossible to achieve in the current onsite-offshore model of engagement. This created more fissures than opportunities to align. So, the inherent inertia and the puritanical interpretation of the methodologies resulted in falling back to the same trap and not reaping the benefits of the natural evolution of management in The Information Technology which was taking its organic spread to lead us to improved effectiveness. But with the onset of COVID 19 pandemic, the Information Technology industry had to take immediate steps, which was, the same steps that were being dictated by the organic spread of the management evolution but were being resisted by this inherent inertia combined with the puritanical approach. Here, the study has analyzed the steps and implications dictated by COVID 19 pandemic in the Information Technology domain, and how it needs to be conceptualized to ensure it is utilized as an enabler for the next phase of The Information Technology management growth, particularly in terms of knowledge work and the knowledge worker..